Ethnically as the cause of political instability in the Gambia ( the case of the 2016-2021 presidential election) - Therese Mendy (Jurnal Ilmiah Mahasiswa Fakultas Ilmu Sosial & Ilmu Politik, 2023)
Ethnic identity does truly matter and plays a substantial role in the political struggle in Africa, as demonstrated by many studies. Ethnic identity is important in Africa because it is crucial to the fight for political dominance. Despite what ethnicity mobilisation has been doing to most African countries, Gambia was enjoying its diversity and ethnic tolerance until early 2016, when the former president of The Gambia, Yahya Jammeh, introduced ethnicity in politics as a tool for mobilising voters. The research method used is an explanatory qualitative approach. This study aims to determine how ethnicity caused political violence during the 2016 and 2021 presidential elections in the Gambia. The study finds that the remarks made by certain ethnic groups and political elites during the campaign have triggered many people's angers, in which they encounter violence in various ways, and that your choice of candidate can also make you face violence. The results of this study suggest that the government in collaboration with all other political organisations in the Gambia strengthen civic education programme to enlighten the citizens about the dangers of associating ethnicity with politics and the repercussions it might have on the country in the near future.Keyword: Ethnicity, Mobilization, Gambia, violence